The aisthetic-sacramental logic of religious feast (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The aim of this article is to describe the fundamental role of the aesthetic experience in the processes of signification of what is usually called “popular religion”. In order to achieve this, we define as the object of our study the religious feast, which, apart from referring to a concrete empirical reality, provides us with two conceptual mediations for our analysis: feast and image. Thus, following a contextualization of our reflection on the field of cultural studies and aesthetics, we proceed to define the aesthetic-sacramental logic of the religious feast on the basis of the concepts “feast” and “image”, from the perspective of the New Material Culture approach.
Keywords: Art; theology; popular religion; religious feast; cult image